Determination of the Chemical Stability of Cyanocobalamin in Medical Food by a Validated Immunoaffinity Column-Linked HPLC Method - Wonjong Lee; Yoon-Bok Lee; Moon Haeng Huh; Jae Kwon Choi (Journal of Food Quality)
Cyanocobalamin, which plays an essential role in the body, is a synthetic form used in medical food. This present study aimed to develop an HPLC analysis method for determination cyanocobalamin and investigate the stability of cyanocobalamin in medical food. Validation of the developed method for cyanocobalamin was evaluated with linearity, LOD, LOQ, and accuracy. The linearity of this method was calculated with a value of the coefficient of determination (R2) ≥ 0.999. LOD and LOQ were 0.165 and 0.499 μg/kg, respectively. The recovery of medical food matrixes for accuracy was more than 97.63%. The validated method was applied for determining cyanocobalamin from medical foods. The developed method was used to examine the additives for cyanocobalamin protection. Ferric chloride and sorbitol alleviated cyanocobalamin degradation from heat and ascorbic acid. Especially, sorbitol showed a superior protective effect during the medical food production process. Therefore, this study suggests that sorbitol is a sweetener additive that prevents cyanocobalamin degradation by heat and the food matrix in medical food processing.